2018
DOI: 10.1186/s12934-018-0907-x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of metabolic module with improved promoter strength increases the productivity of 2-phenylethanol in Saccharomyces cerevisiae

Abstract: Background2-phenylethanol (2-PE) is an important aromatic compound with a lovely rose-like scent. Saccharomyces cerevisiae is a desirable microbe for 2-PE production but its natural yield is not high, and one or two crucial genes’ over-expression in S. cerevisiae did not improve 2-PE greatly.ResultsA new metabolic module was established here, in which, permease Gap1p for l-phenylalanine transportation, catalytic enzymes Aro8p, Aro10p and Adh2p in Ehrlich pathway respectively responsible for transamination, dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…We designed a third module (III) for production of the acyl donor 1-O-β-phenyllactoylglucose (PLA glucoside) from phenylalanine via aromatic aminotransferases Aro8 and Aro9, phenylpyruvate reductase (PPR) and PLA UDP-glucosyltransferase (UGT84A27) 16 . Yeast produce 3-phenylpyruvate from phenylalanine via Aro8 and Aro9 21 , and wild-type yeast and CSY1251 produce trace levels of PLA, potentially via nonspecific activity of a lactate dehydrogenase (LDH) acting on 3-phenylpyruvate 22 . We screened PPRs from E. coli 23 , Lactobacillus (UniProt A0A2U9AUW1), A. belladonna 24 and Wickerhamia fluorescens 25 and LDHs from Bacillus and Lactobacillus with reported activity on 3-phenylpyruvate 22,26,27 via expression from a plasmid in CSY1251.…”
Section: Ta Acyl Acceptor and Donor Biosynthesismentioning
confidence: 99%
“…We designed a third module (III) for production of the acyl donor 1-O-β-phenyllactoylglucose (PLA glucoside) from phenylalanine via aromatic aminotransferases Aro8 and Aro9, phenylpyruvate reductase (PPR) and PLA UDP-glucosyltransferase (UGT84A27) 16 . Yeast produce 3-phenylpyruvate from phenylalanine via Aro8 and Aro9 21 , and wild-type yeast and CSY1251 produce trace levels of PLA, potentially via nonspecific activity of a lactate dehydrogenase (LDH) acting on 3-phenylpyruvate 22 . We screened PPRs from E. coli 23 , Lactobacillus (UniProt A0A2U9AUW1), A. belladonna 24 and Wickerhamia fluorescens 25 and LDHs from Bacillus and Lactobacillus with reported activity on 3-phenylpyruvate 22,26,27 via expression from a plasmid in CSY1251.…”
Section: Ta Acyl Acceptor and Donor Biosynthesismentioning
confidence: 99%
“…In addition, deficiency of NADH and/or L-Phe may limit the efficiency of 2-PE synthesis in the Ehrlich pathway. It has been demonstrated that when GDH2, GAP1, ARO8, ARO10, and ADH2 were coexpressed in S. cerevisiae YS58, the intracellular level of L-Phe was increased and NADH was regenerated, leading to the concentration of 2-PE increasing to 6.3 g/L (Wang et al, 2018).…”
Section: -Pe Synthesis Via the Ehrlich Pathway Major Enzymes Of The mentioning
confidence: 99%
“…It has been demonstrated that overexpression of ARO80 can upregulate the transcription levels of ARO9 and ARO10, resulting in a significant increase in the 2-PE titre (Kim et al, 2014). Similarly, modification of the GATA factor can also effectively improve the efficiency of 2-PE synthesis; for example, overexpression of GLN3 and GAT1 in S. cerevisiae YS58 led to an increase in 2-PE production (Wang et al, 2018).…”
Section: -Pe Synthesis Via the Ehrlich Pathway Major Enzymes Of The mentioning
confidence: 99%
“…Up to date, various metabolic engineering strategies have been implemented in E. coli and S. cerevisiae to improve aromatics production, including expression of the feedback-insensitive DAHP synthases 38 and chorismite synthase, enhancing the shikimate pathway 39 and modular microbial coculture 4042 . A number of studies have been focused on optimizing the endogenous Ehrlich pathway to produce 2-phenylethanol up to 3-6 g/L 4345 , however, the expensive precursor L-phenylalanine was fed into the bi-phasic bioreactors 46, 47 , restricting its economic potential for large-scale production. The highest titer of 2-phenylethanol production from the de novo shikimate pathway was reported recently as 1.58 g/L (13 mM) from S. cerevisiae 38 .…”
Section: Introductionmentioning
confidence: 99%